Study of the impact of some liver enzymes (GOT, GPT, ALP) for the employees at the Tuwaitha nuclear site. - Aliwy Finteil, Samira; Salih Jabbar, Ali; Ibrahim Abdul Majeed, Qabas (Journal of Madenat Alelem University College, 2019)
Background: Al Tuwaitha is the center of radiation activity in Iraq and which includes several directorates that have radioactivity such as radioactive waste removal and storage of radioactive sources as well as contain a reactor and a hot cell. In this study, the level of some liver enzymes was determined as the liver is the largest organ in the body and more sensitive to radiation for employees in different site in Tuwaitha and comparison the level of these enzymes with the level of liver enzymes to other people from outside Tuwaitha (as control) that do not contain radioactive activity. The aim: this study aims to determine the effects of radiation on the level of liver enzymes and to investigate the health of employees. Method: The level of enzymes was measured by kinetic method using the ready kit (French agappe) and the work all done in the laboratories of the radioisotopes department for the period from 2/1 to 30/5 of 2017. The blood samples were taken from a number of employees at different site in Al-Tuwaitha and a number outside the Tuwaitha site. The control group was compared to the employees. The groups ranged in age from (35 - 55 years) and their weight between (70 - 95 kg). The results were statistically analyzed using spss (version 20). Results: The results were compared to the mean between two groups it showed no significant differences (p> 0. 05) for the three enzymes between two groups. Conclusion: Regularly evaluates the exposed doses of each employee along with the necessary health assessments. Normal values of concentration liver enzymes/ (GOT, GPT, ALP) and may ensure a good hepatic health of the radiation-exposed employees.